Solar Radiation Alters Toxicity of Carbofuran: Evidence from Empirical Trials with Duttaphyrnus melanostictus - M.R. Wijesinghe; B.A.D.M.C. Jayatillake; W. D. Ratnassoriya (Journal of Tropical Forestry and Environment, 2011)
In the present study we investigated the potential of natural solar radiation to alter the toxicity of a commonly used carbamate pesticide, carbofuran, on tadpoles of the Common Asian Toad Duttaphrynus melanostictus. A single exposure trial was conducted over 96 hrs with three concentrations (150, 250 and 500 µgl-1) of photo-irradiated and non-irradiated carbofuran. Results show that photo-irradiation markedly reduced the toxicity of carbofuran as evident by its effects on three end points, i.e. mortality, growth and swimming activity. The mortality of tadpoles exposed to irradiated carbofuran was significantly lower than those exposed to the non-irradiated pesticide. Both treatment and control tadpoles showed a hormetic response for mortality. Tadpoles in irradiated tanks were also larger and more active than those in the control tanks. Photo-altered toxicity was evident at all three tested concentrations. The results of this study therefore signals caution when directly linking  results of empirical trials to field scenarios and highlight the necessity to evaluate toxic effects of compounds under variable environmental conditions.